Implementation of government regulation on Disposable Plastic Reduction at Surabaya - Siti Umi Hanik; Maritha Nilam Kusuma (Faculty of Civil Engeneering and Planning - ITATS, 2022)
Plastic has the advantage of being durable, cheap, and easy to get everywhere and we are increasingly dependent. And most of the plastics we use are single-use plastics, as a result, if they are not managed properly, they will become waste and have a negative impact on the environment. With the decomposition period which is too long, which is 100-500 years, this will be a problem if it is not managed properly, such as being burned which has a bad impact on health, or being disposed of carelessly in the end until it reaches the sea and will cause damage to the marine ecosystem. The issuance of Mayor Regulation No. 16 of 2022 which regulates the reduction of single-use plastic in the city of Surabaya is expected to maintain environmental sustainability and reduce the generation of waste entering the Final Processing Site. The purpose of this study is to know or analyze the extent of the implementation of Mayor Regulation No. 16 of 2022 regarding the reduction of single-use plastic in the city of Surabaya. The research method used is normative juridical, namely by analyzing problems based on applicable regulations and also the literature that discusses the problem. And the results of this study are that it can be stated that these regulations, namely regulations for reducing single-use plastics, can be obeyed and carried out well by several parties, namely from the community, business actors, modern shops, retail, restaurants, hotels, and supermarkets. And there needs to be socialization, and monitoring for the enforcement of this regulation so that it is carried out optimally.